2010
DOI: 10.1016/j.jacc.2009.10.061
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Cardiovascular Events and All-Cause Mortality With Arterial Stiffness

Abstract: Aortic stiffness expressed as aortic PWV is a strong predictor of future CV events and all-cause mortality. The predictive ability of arterial stiffness is higher in subjects with a higher baseline CV risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

82
2,744
7
159

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 3,629 publications
(2,992 citation statements)
references
References 47 publications
82
2,744
7
159
Order By: Relevance
“…This association is in line with previous, smaller observations 8, 29. Both reported a higher risk (6.15% versus 1.6% risk per year) of developing CVD per SD increase in aortic PWV.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This association is in line with previous, smaller observations 8, 29. Both reported a higher risk (6.15% versus 1.6% risk per year) of developing CVD per SD increase in aortic PWV.…”
Section: Discussionsupporting
confidence: 92%
“…In aortic PWV studies, MI was often included in the definition of outcome variables such as overall CVD events or CHD, but not investigated as an individual outcome as has been done in this study. These previous studies show an association between aortic PWV and CHD,8, 31, 32, 33 as is shown here as well. Our results are consistent with previous PP studies that reported associations with both incident MI3 and CHD34 after adjustment for traditional CVD risk factors in a hypertensive and community‐based cohort, respectively.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This increases systolic blood pressure and arterial pulse pressure (the difference between systolic and diastolic blood pressure), as well as the ‘pulsatility’ of blood flow, which is transmitted to the microvasculature of vulnerable high‐flow organs such as the brain and kidney, causing end‐organ damage and other pathophysiological effects (Lakatta & Levy, 2003; Mitchell et al ., 2010; Mitchell, 2014). Here, we show that 8 weeks of NMN supplementation reverses the age‐associated increase in two functional indices of aortic stiffness: aPWV, the gold standard clinical measure of large elastic artery stiffness (Mitchell et al ., 2010; Vlachopoulos et al ., 2010), and the elastic modulus, an in vitro measure of the intrinsic mechanical properties of arteries (Humphrey, 2002; Akhtar et al ., 2011; Fleenor et al ., 2012b) (Fig. 3A,B).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated aortic stiffness is an independent predictor of cardiovascular events and all‐cause mortality in healthy1 and diseased2, 3 populations. The mechanisms responsible for increased central artery stiffness, measured most commonly as carotid‐femoral pulse wave velocity (cf‐PWV),4 are not fully understood and complex.…”
Section: Introductionmentioning
confidence: 99%